National Strategies for Preventing and Managing Non-communicable Diseases in Selected Countries - Gassner, Lucia; Zechmeister-Koss, Ingrid; Reinsperger, Inanna (Frontiers in Public Health, 2022)
Non-communicable diseases (NCDs) are the leading cause of death worldwide and are responsible for a high burden of disease. Many countries have developed national strategies for the management and prevention of NCDs to improve the care of chronically ill people or prevent NCDs. This article aims to provide an overview of national NCD strategies from selected countries and their implementation. The focus was on cardiovascular and chronic respiratory diseases, diabetes type II, and depression. A comprehensive, structured hand search was conducted in various databases and websites for national strategies on the 4 NCDs. According to pre-defined criteria, 18 strategies from 8 countries (Germany, Switzerland, Netherlands, Finland, Ireland, United Kingdom, Canada, Australia) were selected. The included NCD strategies differ considerably in terms of level of detail, structure and implementation. All strategies include information on planned activities, but only a few provide detailed information on these interventions, including their evaluation. A structured approach from the macro to the micro level seems crucial for a comprehensive, coordinated overall policy. Strategies should be evaluated regularly using appropriate methods to measure target achievement. For the prevention and management of NCDs, it is important to start in early childhood and to adequately consider the social determinants of health with a ‘Health in All Policies’ approach.